CRIMINAL LEGAL PROTECTION OF PEOPLE'S HEALTH - Risteski, Temelko; Spirkoska, Biljana; Mihtaroski, Emrah (Institute of knowledge management, 2023)
Abstract: The health, after the life, is the second most important biological value of man as an individual. It is directly related to life. The dialectical opposite of health is disease. Health facilitates and sustains a person's life, while illness complicates and destroys it. Health is not only a personal value of a person, but a social value. Social activities, be they manual or mental, can only be performed effectively by healthy people. Therefore, the protection of people's health is subject to the constitutional and legal normative regulation of the states. The Constitution of the Republic of North Macedonia, in Article 39, guarantees, every citizen of the Republic, the right to health care. The Constitution gives every citizen the right, and obliges him, to protect and improve his own health and the health of others. The health care of the citizens of the Republic of North Macedonia is subject to the regulation of more than twenty laws in the field of health. Of these, the Law on Health Care, the Law on Public Health, the Law on the Protection of Patients' Rights and the Law on Medicines and Medical Devices are undoubtedly the most significant. Violation of the provisions of these and other laws is sanctioned by the misdemeanor’s protection provisions contained therein. The criminal legal protection of human values, be they personal or social, is ensured by the criminal legislation of the state. Immediate criminal legal protection is regulated by the criminal laws of the states. In the Republic of North Macedonia it is regulated by the Criminal Code. This code also regulates the criminal legal protection of people's health, as a personal and social value. The Code prescribes several criminal offenses against people's health. They are contained in its twenty-first chapter entitled "Criminal offenses against human health.” The perpetrators of these offenses are persons who directly perform health care work (doctors and other health workers), persons who indirectly participate in the performance of these works (pharmacists or other persons authorized to prepare or dispense medicines and veterinarians or other authorized veterinary workers) and other persons.